Patient Advisors: How to implement a process for involvement at all levels of governance in a healthcare organization - Marie-Pascale Pomey; Edith Morin; Catherine Neault; Veronique Biron; Lise Houle; Louise Lavigueur; Guy Bouvette; Nicole St-Pierre; Martin Beaumont (The Beryl Institute, 2016)
Patient involvement at the operational (clinical care and services), tactical (management), and strategic (board of directors and executive management) levels of establishments is increasingly sought after. To address this specific challenge, a Canadian healthcare organization, the Centre intégré universitaire de santé et de services sociaux de la Mauricie-et-du-Centre-du-Québec, has developed an integrated strategy based on three principles: (1) shared leadership between a patient and a manager to build the strategy; (2) a clear process for recruiting, training, and coaching patient advisors (PA) so that they can participate in decision-making at the various levels of governance of the establishment; and (3) a feedback process for improving the strategy over time. This initiative gave rise to a pool of 30 patient advisors who reviewed documentation (39.07%), presented testimonies to establishment practitioners (13.73%), participated in process improvement activities (12.97%) and committees (8.93%), and helped train students in health sciences (11.61%). It also led to the development of a request form for all persons wishing to involve PAs in their projects. This PA involvement, highly appreciated by both managers (94%) and PAs (81%), brought back the fundamental meaning of the patient-practitioner relationship and helped incorporate patients' experiential knowledge into the care and service improvement process. This strategy can serve as a model for other organizations wishing to structure optimal patient engagement at the different levels of governance of their organization.